Utilization Of Electronic Mail And Teaching Effectiveness Of English Language Teachers’ In Secondary Schools In Abak Local Government Area, Akwa Ibom State-Nigeria - Ema, Iniobong Bassey; Etim, Paulinus J. (Advances in Social Sciences Research Journal, 2017)
The advents of internet and Globalization have brought diversified activities in all aspects of human endeavour including the classroom. The introduction of instructional technologies in the classroom has caused a lot of researches in generating innovative pedagogical strategies to improve classroom communication. This study was therefore on utilization of electronic mail and Teaching effectiveness of English Language Teachers in secondary schools in Abak Local Government Area of Akwa Ibom State –Nigeria. Technology Acceptance model and Diffusion of innovative theories were also used as a foundation for the study. This study adopted the descriptive survey design. Two hypotheses were raised to direct the study. There are 76 graduate English teachers in the 15 public secondary schools in Abak Local Government Area. Simple random sampling technique of hat and draw method was used to select 68 English Language teachers for the study. Researchers developed instrument tagged “Teachers Utilization of e-mail and Teaching Effectiveness Questionnaire (TUETEQ) was used to elicit information from the respondents. The instrument was face, content and criterion validated by two experts all in the Faculty of Education, University of Uyo, Uyo. Split half strategy was done using 12 English Language Teachers in the study area that were not used for the main study. Pearson Product Moment Correlation Co-efficient analysis was used to get the r-value. This value was further treated to Spearman Brown Prophetic formular to get reliability co-efficient of .83. The questionnaire copies were administered to the respondents by the researchers and the copies were collected on the spot after completion. Their responses were coded and used for analysis using t-test statistics. Results of the analysis showed a significant influence of use of e-mail and teachers attitude on teaching effectiveness of English Language. Recommendations were made to improve the teaching of English Language to include among others that teachers of English Language should adopt the use of e-mail as innovative instructional strategy and that teachers should be trained to become computer literates for easy access to e-mail and thus promoting effectiveness of teaching.